1984
DOI: 10.1104/pp.75.2.311
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Pod Removal on Metabolism and Senescence of Nodulating and Nonnodulating Soybean Isolines

Abstract: ABSTRACrField studies were condcted in 1981 and 1982

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
23
0
1

Year Published

1984
1984
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 16 publications
4
23
0
1
Order By: Relevance
“…5), but leaf senescence was not altered. Thus, even though leaf P does decline in some cases during the seed filling period in soybean (13,14,18), this decline is not a factor in the regulation of the senescence process. It has been consistently demonstrated that monocarpic leaf senescence is associated with declines in leaf N as manifested by degradation of the photosynthetic apparatus (2,3,7,19,28,29). The results of this study were consistent with this observation.…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…5), but leaf senescence was not altered. Thus, even though leaf P does decline in some cases during the seed filling period in soybean (13,14,18), this decline is not a factor in the regulation of the senescence process. It has been consistently demonstrated that monocarpic leaf senescence is associated with declines in leaf N as manifested by degradation of the photosynthetic apparatus (2,3,7,19,28,29). The results of this study were consistent with this observation.…”
Section: Resultssupporting
confidence: 82%
“…Leaf P concentration did not increase until the soil P level exceeded that required for maximum growth. Leaf senescence is often characterized by a large decrease in leaf N during the seed filling period (2,3,7,19,28,29). For all soil P treatments used in this study, there was a large decline in N concentration during the seed filling period (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Analysis of photosynthetic processes revealed that carbon fixation rates declined progressively from the time of full leaf expansion (Figure 4). This age-related, progressive loss of photosynthetic function from the time of leaf maturity may be a general feature of annual plants because this phenomenon has been observed in cucumber (Callow, 1974), Perilla (Batt and Woolhouse, 1975), barley (Friedrich and Huffaker, 1980), wheat (Peoples et al, 1980), maize (Crafts-Brandner et al, 1984a), and soybean (Wittenbach, 1982;Ford and Shibles, 1988). Wittenbach referred to the photosynthetic decline as "functional senescence" to distinguish this process from the subsequent rapid loss of chlorophyll and macromolecular turnover associated with the senescence syndrome (Wittenbach, 1983).…”
Section: Discussionmentioning
confidence: 99%
“…tissues (Crafts-Brandner et al, 1984a). The source of carbon for sucrose synthesis in this case is unlikely to be photosynthesis, but is rather through the P-oxidation of lipids because glyoxysomal pathways are known to increase during senescence (Gut and Matile, 1988;DeBellis et al, 1990).…”
Section: (C) Rbcs (D) Ef-1a (E) Sag2 (F)sag4mentioning
confidence: 99%
“…Analysis of variance and combined analysis were conducted as previously described (3). An overall LSD (compares between treatments at each sampling time and within treatments across sampling times) was calculated from error B in the split plot design and was included on figures to give a general indication of treatment differences.…”
mentioning
confidence: 99%